PENGARUH ATTRACTION, ACCESSIBILITY DAN AMENITIES TERHADAP LOYALITAS WISATAWAN PADA PANTAI KARANG HITAM LEKOK KABUPATEN PASURUAN - Azhura, Nisa; Fibriyani, Vita; Subagio, Dyajeng Puteri Woro (Yayasan Education and Social Center, 2024)
Industry is a significant economic driver in a region which is the basis for economic expansion. Activities related to marine tourism include beach tourism. Karang Hitam Beach is one of the tourist destinations in Pasuruan. This research aims to determine the influence of attraction, accessibility and amenities on tourist loyalty at Karang Hitam Lekok beach, Pasuruan Regency. The population in this study were visitors who had visited Karang Hitam beach who lived in the Tapal Kuda area, with a sampling method, namely purposive sampling. Using the Hair formula, with a sample size of 65 respondents. The research results show that 1) attraction, accessibility and amenities simultaneously influence tourist loyalty with a significance value of 0.000 with a variable determinant coefficient (R2) of 0.548 which shows that attraction, accessibility and amenities can influence tourist loyalty by 54.8% while the remaining 45.2% is influenced by other variables outside this research. 2) attraction partially has a significant effect on tourist loyalty with a significance value of 0.001. 3) partial accessibility has a significant effect on tourist loyalty with a significance value of 0.044. 4) amenities partially have a significant effect on tourist loyalty with a significance value of 0.005